Exploring How Workload and Work Environment Propel Education Personnel's Performance through Work Motivation - Kurniawan, Yanto (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
Education personnel are valuable assets or capital in addition to other capital, in carrying out their duties, of course, education personnel will carry out in accordance with the SOP that has been set. The purpose of this study is to analyze and test the effect of workload and work environment on work motivation that has an impact on the performance of education personnel both partially and simultaneously. The method in this study is with a descriptive and quantitative approach. The sample in this study amounted to 110 respondents and used saturated sampling techniques. The analysis tool uses linear regression analysis. The result of this study is that there is a partial positive and significant influence between workload on work motivation shown by tcalculate > ttable (5.553 > 0.1873), with a significant value (0.000 < 0.0.5). There is a partial positive and significant influence between the work environment on work motivation, which is shown by the tcalculate > table (7.559 > 0.1873) with a significant value (0.000 < 0.05)